Skills and Competencies for Effective Academic Advising and Personal Tutoring - McGill, Craig M.; Ali, Mehvash; Barton, Dionne (Frontiers in Education, 2020)
Advising/personal tutoring has moved from the fringes of higher education to the center of student success initiatives. Advising professionals serve as faculty members, mentors, student advocates, and campus leaders. Drawing upon data from an empirical investigation regarding the professionalization of academic advising, we examine the critical aspects related to performing effective academic advising and personal tutoring. Using directed qualitative content analysis, data were examined for evidence of professional values, professional skills, professional behaviors, training, and continuing professional education and development. We consider the findings in comparison to NACADA’s Core Values, the John N. Gardner Institute for Excellence in Undergraduate Education in support of student success by promoting excellence in academic advising (EAA), NACADA’s Core Competencies of Academic Advising, Council for the Advancement of Standards in Higher Education (CAS) Standards, UKAT Professional Framework for Advising and Tutoring, and United Kingdom’s National Occupational Standards.